The Insidious Dr. Fu Manchu - Rohmer, Sax, 1883-1959 (Salt Lake City, UT : Project Gutenberg, 1994)
"The Insidious Dr. Fu Manchu" by Sax Rohmer is a novel published in 1913. When Nayland Smith arrives unexpectedly from Burma, Dr. Petrie learns of a sinister threat: the brilliant Chinese criminal Dr. Fu Manchu is targeting men connected to India. Through London's opium dens and English country estates, Smith pursues this master poisoner and chemist, who leads a mysterious "Third Party" and seeks to capture Europe's best engineers for an unknown purpose. But Fu Manchu proves a cunning adversary who outwits his pursuers at every turn. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Mystery_of_Dr._Fu-Manchu
Release date is 1994-10-01
This etext was updated by Stewart A. Levin of Englewood, CO
Keywords: Detective and mystery stories; Fu Manchu, Doctor (Fictitious character) -- Fiction; Criminals -- Fiction